2018
DOI: 10.1186/s13643-018-0874-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of cervical cancer in HIV-seropositive women from developing countries through cervical cancer screening: a systematic review

Abstract: BackgroundThere is scanty or inconclusive evidence on which cervical cancer screening tool is effective and suitable for human immunodeficiency virus (HIV)-seropositive women. The aim of this review was to assess, synthesise and document published evidence relating to the available cervical cancer screening modalities for HIV-seropositive women in developing countries. This paper did not review the issue of human papillomavirus (HPV) prophylactic vaccine on HIV-seropositive women.MethodsFive electronic databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 61 publications
3
45
0
Order By: Relevance
“…The HPV prevalence in WLWH reported in this study was lower than observed in some populations [16][17][18][19][20][21][22], comparable to some populations [18;23-26], and higher than in other populations [18;27] living in SSA. We observed, as seen in other studies, that HIV status [24;27] was an independent predictors of HPV prevalence in WLWH.…”
Section: Discussionsupporting
confidence: 56%
“…The HPV prevalence in WLWH reported in this study was lower than observed in some populations [16][17][18][19][20][21][22], comparable to some populations [18;23-26], and higher than in other populations [18;27] living in SSA. We observed, as seen in other studies, that HIV status [24;27] was an independent predictors of HPV prevalence in WLWH.…”
Section: Discussionsupporting
confidence: 56%
“…Thus, our findings may suggest in part that sex-specific mortality differences do not reflect inherently better health behaviors among women compared to men, but rather access to reproductive health services and earlier HIV care entry among younger women, and a lack of similar benefit among older women who do not access such services [4,13]. It is well-established that HIV-positive women are at increased risk for the development of cervical cancer [71]. Cervical cancer is the most commonly diagnosed cancer among women in Zambia, with the highest proportion of registered cases concentrated among those 40-60 years old [72].…”
Section: Plos Medicinementioning
confidence: 83%
“…Cervical cancer is the most commonly diagnosed cancer among women in Zambia, with the highest proportion of registered cases concentrated among those 40-60 years old [72]. While data regarding cervical cancer were not available as part of our study, it is possible that delayed and missed diagnoses of cervical cancer may have also contributed to the high mortality rate observed among older women, and, therefore, continued scale-up and availability of screening [71] coupled with early ART and retention in HIV services [73] might be an important intervention to address mortality among older HIV-positive women. We also observed that less than 30% of women �50 years old were married (with more than 30% reporting being widowed), a marked difference from the nearly two-thirds of men �50 years old reporting being married.…”
Section: Plos Medicinementioning
confidence: 97%
“…3,5,8 Although advantageous in many regards, HPV DNA testing has the trade-off of having relatively low specificity, 7,[9][10][11] particularly in women living with HIV. 5,12 In the screen-and-treat model, now widely recommended as the most appropriate approach for low-resource settings, the relatively low specificity of HPV DNA testing means that sizable numbers of women may be overtreated for transient infections that will ultimately regress. 13 Scarce resources would be unnecessarily spent on women at low risk for CIN2+ being referred for further colposcopy follow-up or treatment.…”
Section: Introductionmentioning
confidence: 99%